The development and activity of the "company of mutual aid of private employees" of Galicia in 1867 - Ihor Berest (Cхід, 2017)
The article analyzes the work of the trade union organization "COMPANY OF MUTUAL AID OF PRIVATE EMPLOYEES" of Galicia in 1867, which in fact became the successor to the dissolved by the Austrian authorities in October 1848, the "Company of Private Employees" of Galicia. The purpose of its activity was to support the moral and material interests of private employees. The society was divided into real, advisory and honorary members, and the bodies of the partnership were the Central Department, the Department of Statistics and the Supervisory Board. Permanent cash aid from a partnership, that is, a pension, could be obtained by every one of his real members after 10 years of impeccable, efficient service as a private employee. In general, the painstaking and persistent organizational work of the central department of the COMPANY OF MUTUAL AID OF PRIVATE EMPLOYEES was crowned with great success. According to the report of the central management of the said organization, for the first year of existence (1868), the Society had 2200 real members with 4100 contributions, 496 members of the advisory members with an annual quota of 6400 florins and 359 benefactors who supported the appeal of the board with one-time donations in the quota of 52 333 fl. 43 tst. Only during the first year of its existence, the "Company of Private Employees" managed to create its departments and centers in 71 districts, which went beyond Galicia, and spread to the land of Bukovina, Western Volhynia, Kholmshchyna, Podlyashshya and other lands. This testified to his great popularity among private servants of the region.